Refined guiding centre approximation for kinetic studies of Nitrogen seeding in medium density ITER L-mode scenarios with EMC3-EIRENE. (October 2022) - Harting, D.; Knieps, A.; Reiser, D.; Rode, S.; Romazanov, J.; Börner, P.; Feng, Y.; Frerichs, H.
Highlights: Improvements of kinetic ion transport module in guiding centre approximation in EMC3-EIRENE. Validation of the kinetic ion transport module against magnetic moment conservation and formation of banana-orbits. First stable simulation of Nitrogen seeding for ITER L-mode scenario with the improved kinetic ion transport module of EMC3-EIRENE.